VD_FINDINFO AP / 2010 / 276 vom 13. November 2009 - VD Tribunal cantonal (2009)
RESTITUTION ANTICIPÉE, BAIL À LOYER, LOCATAIRE DE REMPLACEMENT | 264 al. 1 CO, 264 al. 2 CO, 264 CO, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 13 LTB